Diseño de una aplicación móvil como herramienta de apoyo digital para el diligenciamiento de la historia clínica de adultos de la universidad Antonio Nariño de Cúcuta (2024)
A semi-structured survey was applied designed to identify the needs for digital support during the completion of adult medical records, with a particular focus on the effectiveness of clinical processes and the acceptance of new technologies among the population studied. This survey was developed in collaboration with experts in research methodology and dental technology. The content of the survey was validated through pilot tests and reviewed by experts, to ensure its reliability and validity, guaranteeing that each element collected is aligned with the innovation objectives and the needs for digital support during the completion of the adult medical history. . , with a particular focus on the effectiveness of clinical processes and the acceptance of new technologies among the population studied. A web application was developed based on the specific needs of the students and was socialized in the classrooms, the design of the graphical interface and the correct use of the application for its best function.